Peran Manajer dalam Membangun Teamwork pada Karyawan: Studi Kasus di Bento Kopi Cibiru - Destiani, Dena; Daniswara, Fidelairna; Oktaviani, Listi Sinta Nur; Ananti, Naila Dwi; Nurasiah, Sofa Parihah (Teewan Journal Solutions, 2026)
This study aims to examine the role of managers in building teamwork among employees of Bento Kopi Cibiru. Teamwork is essential to the smooth operation of a coffee shop, which requires rapid coordination across roles such as cashiers, baristas, and service staff. This study employs a qualitative method with a descriptive approach, with data obtained through in-depth interviews and observation of the manager as the key informant, then analyzed using the Miles and Huberman interactive technique, comprising data reduction, data display, and conclusion drawing. The findings indicate that the manager plays an important role in building teamwork through three main functions: acting as a role model in work attitude, maintaining open communication through routine briefings, and serving as a mediator in resolving conflicts among team members. The team structure, though hierarchical, remains flexible, allowing members to assist one another during high workloads, while motivational strategies such as bonding activities and performance recognition further strengthen team cohesion. Communication proved to be the primary foundation underpinning mutual trust and shared commitment within the team. This study is expected to provide empirical contributions regarding the role of managers in building teamwork in coffee shop businesses